Using Fish Oil to Prevent Anthracycline-Induced Cardiotoxicity. (29th May 2020) - Angelotti, Austin; Snoke, Deena; Cole, Rachel; Belury, Martha
Abstract: Objectives: Due to the established cardioprotective effects of fish oil in pressure-induced models of heart failure, we hypothesize that fish oil could also be cardioprotective in anthracycline-induced heart failure. Methods: In a mouse model of anthracycline cardiotoxicity male mice were assigned to one of four groups: anthracycline injection + control diet, saline injection + control diet, anthracycline injection + fish oil diet, or saline injection + fish oil diet. The control diet contained 90 g/kg soybean oil while the fish oil diet contained 40 g/kg soybean oil and 50 g/kg fish oil (8% fat by weight). The differences between groups were assessed by two-way ANOVA. Sidak's multiple comparison test was used to determine differences from the control group. Results: Controlling for body weight, anthracycline treatment increased heart weight in both diet groups suggesting cardiac hypertrophy. Compared with control diet, fish oil diet attenuated anthracycline-induced increases in pro-inflammatory Il6 and pro-fibrotic collagen III mRNA. In addition, dietary fish oil increased bcl2 (anti-apoptosis) and heme oxygenase-1 (antioxidant) mRNA in heart muscle in mice treated with anthracycline. Conclusions: Our data suggest that dietary fish oil may attenuate some of the cardiotoxic effects of anthracyclines. Fish oil is generally found to be safe in cancer patients, and if effective in clinical trials could provide a widely available therapy for cancer patients undergoing anthracycline chemotherapy. Funding Sources: Funding was provided by NIH R21CA185140, Ohio Agriculture Research and Development Center, the Carol S. Kennedy Professorship, and the Ohio State University Education and Human Ecology Dissertation Research Fellowship.